2004
DOI: 10.1103/physrevb.69.174411
|View full text |Cite
|
Sign up to set email alerts
|

Diameter dependence of ferromagnetic spin moment in Au nanocrystals

Abstract: Au nanoparticles exhibit ferromagnetic spin polarization and show diameter dependence in magnetization. The magnetic moment per Au atom in the particle attains its maximum value at a diameter of about 3 nanometer (nm) in the Magnetization-Diameter curve. Because Au metal is a typical diamagnetic material, its ferromagnetic polarization mechanism is thought to be quite different from the ferromagnetism observed in transition metals. The size effect strongly suggests the existence of some spin correlation effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
157
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 10 publications
8
157
1
3
Order By: Relevance
“…However, this analysis of the size dependence, in particular of the surface magnetization, has recently come under criticism [70]. A re-interpretation by He shows an increasing and leveling of surface magnetization [70], instead of the declining surface magnetization with increasing particle diameter reported by Hori [55]. Hori and co-workers also investigated dodecanethiol (CH 3 (CH 2 ) 11 SH)-capped Au nanoparticles, but found greatly reduced saturation magnetizations compared to Au-PVP.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this analysis of the size dependence, in particular of the surface magnetization, has recently come under criticism [70]. A re-interpretation by He shows an increasing and leveling of surface magnetization [70], instead of the declining surface magnetization with increasing particle diameter reported by Hori [55]. Hori and co-workers also investigated dodecanethiol (CH 3 (CH 2 ) 11 SH)-capped Au nanoparticles, but found greatly reduced saturation magnetizations compared to Au-PVP.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…In addition to polymer-encapsulated [19,54,55,60,61,78] and alkanethiol-coated nanoparticles [24,40,[44][45][46][47][48][49][51][52][53], magnetism has now been observed in Au nanoparticles coated with ligands such as thiolated sugars [41,42] and biomolecules [48,51], thiolated azobenzenes [58,59], phosphine [53], and oleic acid and/or oleic amine [43,57]. The behaviors range from permanent, ferromagneticlike at room temperature, to superparamagnetic, to paramagnetic.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The diamagnetic backgrounds of the Si substrates were subtracted from the raw data. Considering that nanoscale Au, Ag may induce weak ferromagnetism, 18,19 we first investigated the magnetic characteristics of the silicon substrates coated with Au or Ag thin films. All substrates without NWs growth showed only diamagnetic behaviors.…”
mentioning
confidence: 99%
“…Superparamagnetic behavior has been reported in Pd and Au nanoparticles embedded in poly͑N-vinyl-2-pyrrolidone͒ at low temperatures with a mean diameter of 3 nm, 8 and recently Hori et al 9 have also reported ferromagnetic behavior in Au NPs with protective agents polyacrylonitrile and polyallyl amine hydrochloride ͑PAAHC-Au͒. Ferromagnetic spin polarization of Au nanoparticles protected by PAAHC with a mean diameter of 1.9 nm has been measured by x-ray magnetic circular dichroism.…”
Section: Structural and Magnetic Characterization Of Oleic Acid And Omentioning
confidence: 99%